Thermodormancy and Germination Response to Temperature of Pyrus ussuriensis Seeds - Zhuolin Liu; Mingyue Li; Meiru Zhu; Rosana López; Roberto L. Salomón; Peng Zhang (Agronomy, 2024)
To determine the optimal germination temperature for Pyrus ussuriensis seeds and whether they experienced the phenomenon of thermodormancy and its inciting factors, several germination tests were conducted using non-dormant P. ussuriensis seeds for comparison. The results showed that the highest germination rate of P. ussuriensis seeds was reached at a constant temperature of 5 °C and variable temperature (night/day) of 5 °C/10 °C. Constant temperatures of 25 °C for three days induced thermodormancy, triggering significant drops in seeding emergence. Thermodormancy was related to the inhibitory effect of endogenous substances in the seed coat and an elevated abscisic acid concentration. The embryo, by contrast, remained non-dormant. Thermodormant and non-dormant seed embryos showed higher germination rates than dormant seed embryos when applied exogenous abscisic acid and gibberellic acid. We found that P. ussuriensis seeds showed thermodormancy; thus, during early spring sowing, high temperatures should be avoided to prevent low seed germination capacity. Additionally, applying exogenous gibberellic acid, shading and increasing soil moisture can be helpful to enhance the species seed germination.